Botanical Medicines Cryptolepis sanguinolenta, Artemisia annua, Scutellaria baicalensis, Polygonum cuspidatum, and Alchornea cordifolia Demonstrate Inhibitory Activity Against Babesia duncani - Zhang, Yumin; Alvarez-Manzo, Hector; Leone, Jacob; Schweig, Sunjya; Zhang, Ying (Frontiers in Cellular and Infection Microbiology, 2021)
Human babesiosis is a CDC reportable disease in the United States and is recognized as an emerging health risk in multiple parts of the world. The current treatment for human babesiosis is suboptimal due to treatment failures and unwanted side effects. Although Babesia duncani was first described almost 30 years ago, further research is needed to elucidate its pathogenesis and clarify optimal treatment regimens. Here, we screened a panel of herbal medicines and identified Cryptolepis sanguinolenta, Artemisia annua, Scutellaria baicalensis, Alchornea cordifolia and Polygonum cuspidatum to have good in vitro inhibitory activity against B. duncani in the hamster erythrocyte model. Furthermore, we found their potential bioactive compounds, cryptolepine, artemisinin, artesunate, artemether, and baicalein, to have good activity against B. duncani, with IC50 values of 3.4 μM, 14 μM, 7.4 μM, 7.8 μM, and 12 μM, respectively, which are comparable or lower than that of the currently used drugs quinine (10 μM) and clindamycin (37 μM). B. duncani treated with cryptolepine and quinine at their respective 1×, 2×, 4× and 8× IC50 values, and by artemether at 8× IC50 for three days could not regrow in subculture. Additionally, Cryptolepis sanguinolenta 90% ethanol extract also exhibited no regrowth after 6 days of subculture at doses of 2×, 4×, and 8× IC50 values. Our results indicate that some botanical medicines and their active constituents have potent activity against B. duncani in vitro and may be further explored for more effective treatment of babesiosis.